A tool for rapid simulation and sizing of hybrid traction systems with fuel cells. (January 2023) - Pugi, Luca; Berzi, Lorenzo; Cirillo, Francesco; Vecchi, Alessandro; Pagliazzi, Viola
Diesel multiple units (DMU) offer an affordable alternative to electric trains on lines in which infrastructural and maintenance costs of electrification are not justified. A further improvement of sustainability involves the abandonment of internal combustion engines in favour of an electric power train sustained by an on-board storage system. In this work, the authors propose a model to perform a rapid simulation of hybrid storage systems based on hydrogen fuel cells, a technology that should be complementary with respect to battery-operated trains. The proposed tool is applied, as a benchmark test case, to a modular passenger train devoted to regional service. Obtained results clearly demonstrate the capabilities of proposed tools and give useful indications for a feasible optimization and integration of fuel cells for railway applications.